Pengaruh Kreativitas, Lingkungan Keluarga dan Jiwa Entrepreneur Terhadap Niat Berwirausaha Mahasiswa Stkip Pgri Tulungagung - Muhammad Irwansyah; Hari Subiyantoro (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2018)
This study aims to determine the influence of creativity, family environment and entrepreneurial spirit to the intention of entrepreneurship of students in the sixth semester of economic education in stkip pgri tulungagung.Populasi research semester VI students as many as 89 students, data collection methods using questionnaires, data analysis using multiple linear regression formula.Results analysis of data Test t tuktilai value t arithmetic (2.167) creativity variable (X1). The variable of the family environment (X2) has a count value (2,426). The entrepreneur (X3) entity variables have a tcount value (2.049.Can concluded partially that "the influence of creativity (X1), family environment (X2) and entrepreneur spirit (X3)entrepreneur(Y) student of economic education semester VI STKIP PGRI Tulungagung academic year 2017 /2018. Test F, show that valueFhitung (23,464).This shows there are positive influence simultaneously creativity variable (X1) and environment family (X2) and entrepreneur spirit (X3) to entrepreneurship intention (Y) student of Economics Education Semester VI STKIP PGRI Tulungagung Academic Year 2017 / 2018.R2 is equal to 0,453 or effective sumbgan from three independent variable that is 45,3% to intention of entrepreneurship ( Y), and by 54.7% were explained by other factors that were not meticulously in this study.